PhotoStory: Mobile Application for Preserving Historical Heritage Using Timeline View - Firdaus, Fakhry Ikhsan; Tolle, Herman; Antariksa; Rizdania, (International Journal of Interactive Mobile Technologies (iJIM), 2023)
This paper proposes a PhotoStory: mobile-based application to record the transformation of buildings, including the condition of the buildings and the surrounding environment, whether caused by natural disasters or other factors. There are still limited systems available for people to see the changes in historical buildings. Some existing applications only focus on collecting photos, but the photos are not timeline-organized. This research aims to design a mobile application system that can separately group the building photos sent by users through a geotagging-based mobile application and then visualize it on a timeline-view layout. Grouped photos will make it easier for users to see and trace the context of the building. Based on the usability tests that have been done, the system obtained a value of 87,27%, with the Efficiency parameter getting the highest value among other usability parameters, which was 94%. The obtain shows that the system has been designed successfully. As a result, users feel satisfied and become more familiar with historical buildings. Furthermore, using a timeline-view layout proves that it can provide good effectiveness to users in understanding the transformation of buildings.